VD_FINDINFO HC / 2013 / 575 vom 22. August 2013 - VD Tribunal cantonal (2013)
CONTRAT D'ARCHITECTE, RÉMUNÉRATION SELON LES PRESTATIONS, FARDEAU DE LA PREUVE | 8 CC, 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH)